Οι Μπέκταση δερβίσηδες: Μερικές πτυχές συνύπαρξης μεταξύ Ελλήνων και Τούρκων στη Μικρά Ασία 1826-1922 - Μπούρα Κατερίνα Α. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1982)
Despite their persecution during the supression of the Janissaries in 1826, the Bektashis were again reestablished in considerable strength by the mid 19th. century. The striking parallels to be found in the Bektashi practices and those of the Greek Orthodox church may have effectively served the purpose of offering a smoother transition to Islam to a great deal of popular Christianity in Asia Minor. Thus down through Ottoman history, the Bektashis played an important role as a link between Christians and Turks, and preserved the culture that developed among the peoples who were living together in Asia Minor the exchange of populations in 1923.